ANALISIS DAYA MINAT PENGUNJUNG HUTAN KOTA PEKANBARU PROVINSI RIAU - Nursaila '; Defri Yoza; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Urban forest became a assessment to every slep of management. This study aims to identify the interests of visitors about infrastructure and natural beauty of Pekanbaru local society and analyze the condition of infrastructure and natural beauty of Pekanbaru local society. Based on visitor interest. Observation and collection of data by distributing questionnaires to the respondents by the number of 100 persons were then analyzed with descriptive qualitative and quantitative descriptive. The results showed that visitor interest of Pekanbaru local society aims to relax, exercise and enjoy the fresh air and natural beauty with 3 to 4 times a week. Analyze of the interests of the visitors about the natural beauty is 41.5% with unfavorable ratings. While the interests of the infrastructure in Pekanbaru local society shows the result 45.5% claimed it was not good. Analyze of the interests of the visitors about the natural beauty is 1.25% claimed it was not good. While the interests of the infrastructure in Pekanbaru local society shows the result of 1.25% claimed it was not good. Analyze of the interests of the visitors about the natural beauty is 33.25% with good ratings. While the interests of the assesment infrastructure in Pekanbaru local society shows the result 42.08% claimed it was not good. Analyze of the interests of the visitors about the natural beauty is 24% with very good ratings. While the interests of the assesment infrastructure in Pekanbaru local society shows the results 11% claimed it was not good. Keywords : Urban forest, Natural beauty, Infrastructure.